2020
DOI: 10.21203/rs.3.rs-44497/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different Patterns of the SARS-CoV-2 Epidemic across Italian Regions: a Hierarchical Clustering on Principal Components approach

Abstract: Italy has experienced the epidemic of severe acute respiratory syndrome coronavirus 2, which spread at different times and with different intensities throughout its territory. We aimed to identify clusters with similar epidemic patterns across Italian regions. To do that, we defined a set of regional indicators reflecting different domains and employed a hierarchical clustering on principal component approach to obtain an optimal cluster solution. As of 24 April 2020, Lombardy was the worst hit Italian region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Family and community clusters of severe COVID-19 infection have been reported early in this pandemic. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…Family and community clusters of severe COVID-19 infection have been reported early in this pandemic. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Family and community clusters of severe COVID-19 infection have been reported early in this pandemic. [27][28] Reported excess deaths estimates were thought to represent misclassified COVID-19 deaths or potentially those indirectly related to the COVID-19 pandemic. It was suggested that this excess number was related to the pandemic itself and not to disease, it was attributed to lack of facilities during the pandemic.…”
Section: Discussionmentioning
confidence: 99%